2008
DOI: 10.2166/wst.2008.670
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing denitrification kinetics at cold temperature using various carbon sources in lab-scale sequencing batch reactors

Abstract: Wastewater treatment plants in the Chesapeake Bay region are becoming more interested in external carbon sources for denitrification. This is in response to the recent regulations to remediate the Chesapeake Bay, which will limit effluent total nitrogen to near 3 mg/L for plants, thus requiring near complete elimination of inorganic nitrogen species. Since sufficient internal carbon is usually not available for complete denitrification, external carbon is needed to supplement internal sources. Of particular in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 10 publications
2
27
0
Order By: Relevance
“…Even though methanol produced the highest increase in SDR with the methanol-acclimated biomass (7 ± 0.3 mg NO 3 gVSS À1 hour À1 ) it was still low compared to other SDRs. Similarly, Mokhayeri et al (2008) found that ethanol could be used with methanol biomass with similar rates to that achieved with methanol. However, Mokhayeri et al (2008) also found ethanol-grown biomass responded rapidly to methanol, suggesting that the two substrates could be used interchangeably to grow respective populations with a minimum lag period.…”
Section: Denitrification In Batch Assays Using Pure Carbon Supplementmentioning
confidence: 78%
See 2 more Smart Citations
“…Even though methanol produced the highest increase in SDR with the methanol-acclimated biomass (7 ± 0.3 mg NO 3 gVSS À1 hour À1 ) it was still low compared to other SDRs. Similarly, Mokhayeri et al (2008) found that ethanol could be used with methanol biomass with similar rates to that achieved with methanol. However, Mokhayeri et al (2008) also found ethanol-grown biomass responded rapidly to methanol, suggesting that the two substrates could be used interchangeably to grow respective populations with a minimum lag period.…”
Section: Denitrification In Batch Assays Using Pure Carbon Supplementmentioning
confidence: 78%
“…The SDRs obtained when using methanol or formate were much lower than those with acetate and ethanol, but were slightly higher than the control (pure primary wastewater as its sole carbon source). Mokhayeri et al (2008) also found ethanol and acetate to be excellent external carbon sources to aid denitrification when comparing methanol, ethanol and acetate. They also used SBRs to acclimate biomass' to a specified substrate and then conducted a series of ex situ SDR assays.…”
Section: Sequencing Batch Reactorsmentioning
confidence: 90%
See 1 more Smart Citation
“…This can be explained by the fact that denitrifying bacteria are more accessible to ethanol than methanol (Baytshtok et al, 2009). Some researchers also reported that ethanol fostered higher specific denitrification rates than methanol (Martin et al, 2009;Mokhayeri et al, 2008;Lu and Chandran, 2010;Salminen et al, 2014). The carbon source in a given system produces a strong impact on denitrifying performance as organic carbon and energy metabolism with diverse pathways form the foundation for heterotrophic growth.…”
Section: Performance Of Mixotrophic Anfb-mbrsmentioning
confidence: 99%
“…These values were much higher than the 1.53-2.57 for sucrose and 1.29 ± 0.21 for wastewater that were gotten from earlier study using the same methodology [11]. The SDNR values for fermented biosolids were also comparable to the 6.1-10.0 SDNR value for methanol [2,7,10], the most studied and commonly used external carbon in US. This shows some genuine potential of fermented and dark-fermented biosolids as external carbon sources…”
Section: Sdnr Of the Two Fermented Biosolidsmentioning
confidence: 58%